The effect of economic learning insert sharia economics, Product Knowledge, Social Environment, and Religiosity on Interest in Savings in Islamic Banks in Darul Ulum Islamic Boarding School Students Jombang - Nur Lita Faridah,; Hakim, Luqman; Sudarwanto, Tri (Technium Social Sciences Journal, 2021)
This study aims to analyze the effect of the research variables including the insertion of Islamic economics, product knowledge, social environment and religiosity on interest in saving at Islamic banks in high school/MA students at Darul Ulum Islamic Boarding School. This research is a quantitative research using ex-post facto method. The population and sample in this study were students of SMA/MA Pondok Pesantren Darul Ulum class XI IIS with a total of 378 and the number of samples used was 100 students. Data collection techniques using a questionnaire. The data analysis technique used multiple linear regression analysis. The results showed that the insertion of Islamic economics learning and the social environment had a significant effect on students' saving interest in Islamic banks, while product knowledge and religiosity variables had no effect on interest in saving in Islamic banks. Simultaneously, the insertion of Islamic economics learning, product knowledge, social environment and religiosity affect the interest in saving in Islamic banks in the students of the Darul Ulum Islamic Boarding School Jombang.